The Analysis of Learning Model in Office Administration Training at Semarang Job Training Development Center - Mujiati, Mujiati; Raharjo, Tri Joko; Rifai RC, Achmad (Journal of Nonformal Education, 2019)
One reason for the high level of secondary and vocational school participation in quality that does not meet the competency standards required by the labor market. The need for new breakthroughs in order to improve the quality of human resources as an effort to prepare students in the world of work. The purpose of this research is to describe and analyze: (1) The learning model that is implemented in the office administration training that refers to the principle of adult training, (2) the readiness of the participants after completing the training. This research uses qualitative approach method. The subject is the section of training, training instructors, FMD team and trainees. Engineering data collection done by observation, interviews, and documentation. Data analysis techniques include the collection of data, data presentation, data reduction and withdrawal of the conclusion. An examination of the validity of the data using triangulation of sources and method. The research results showed that: (1) the model of learning which is implemented in office administration training refers to information processing model, personal model and behavior modification model. Implementation of the three models includes: learning syntax, social systems, reaction principles, support systems, instructional impacts and impact accompaniment. In the implementation of learning model in office administration, the training is based on adult learning principle, (2) participants' readiness is nurtured through job training activities that include 14 competency units, softskills activities, and character building.